A sodium ion battery negative electrode hard carbon material and preparation method thereof, and a sodium ion battery
By using radiation grafting technology to introduce heteroatoms and perform high-temperature carbonization treatment in the negative hard carbon materials of sodium ion batteries, the problems of insufficient performance of existing hard carbon materials and difficulty in efficient recycling of waste polyolefin materials are solved, and efficient and low-cost hard carbon materials are achieved, which improves battery performance and economic benefits.
Patent Information
- Application Number
- CN202311730039.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-15
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-12-15
AI Technical Summary
The first time the existing sodium ion battery negative hard carbon materials have low efficiency, pore utilization and energy density, resulting in limited application. At the same time, waste polyolefin materials are easy to decompose when preparing hard carbon materials at high temperatures, making it difficult to achieve high carbon yield.
Irradiation grafting technology is used to introduce heteroatoms into polyolefin materials, and hard carbon materials are prepared by high-temperature carbonization treatment. The specific steps include sonicating the polyolefin material in anhydrous ethanol, followed by irradiation grafting treatment in an irradiation grafting solution, followed by washing and high temperature carbonization treatment.
The yield and performance of hard carbon materials are improved, economic benefits are enhanced, and the preparation method is simple and the cost is low. The circulation and rate performance of hard carbon materials are also significantly improved.
Smart Images

Figure CN117699773B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of batteries, and in particular to a sodium ion battery negative electrode hard carbon material and a preparation method thereof, and a sodium ion battery. Background Art
[0002] With the rapid development of 3C electronic equipment, two-wheeled electric vehicles, mobile energy storage and other industries, the public's demand for safe, high-energy-density, long-cycle and stable energy storage equipment has greatly increased. As a secondary energy storage battery that has gradually become popular in recent years, sodium-ion batteries have the advantages of abundant sodium resources and low cost, high battery safety, higher energy density than lead-acid batteries, good high and low temperature performance, and compatibility with lithium-ion battery production lines.
[0003] Negative electrode materials are one of the keys to the development of sodium-ion batteries, and currently the most commonly used are hard carbon materials. Hard carbon refers to carbon that is difficult to graphitize, which is the pyrolysis carbon of high molecular polymers. It has the advantages of high specific capacity, good cycle performance, and good cycle stability at high rates. However, most of the hard carbon materials currently under research have low first coulombic efficiency, pore utilization, and the resulting energy density and platform capacity, making it difficult to further promote the application of hard carbon.
[0004] In addition, with the rapid development of petroleum refining technology and the extensive use of plastic products, polyolefin products are flooding people's lives, resulting in an increase in waste polyolefin materials year by year. How to recycle and process the increasing amount of polyolefin materials is an urgent problem that needs to be solved. The cost of preparing hard carbon materials for the negative electrode of sodium ion batteries using waste polyolefin materials is low, and it can turn waste into treasure, with great cost advantages and economic benefits. However, the performance of carbon materials obtained by different treatment methods is not uniform, and polyolefin materials are easy to decompose when preparing hard carbon materials at high temperatures, making it difficult to achieve a high carbon yield. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for preparing a sodium ion battery negative electrode hard carbon material, thereby improving the carbon yield of hard carbon prepared by using waste polyolefin materials. The method is simple and low in cost.
[0006] In order to solve the above technical problems, the present invention provides a method for preparing a sodium ion battery negative electrode hard carbon material, comprising the following steps: Step 1: adding a polyolefin material to anhydrous ethanol solvent and soaking it for ultrasonic treatment, washing the treated polyolefin material with anhydrous ethanol and then drying it to obtain a pretreated polyolefin material, wherein the pretreated polyolefin material removes impurities covered on the surface of the waste polyolefin;
[0007] Step 2: adding the pretreated polyolefin material in step 1 to the irradiation grafting solution and performing irradiation grafting treatment with neutron beam radiation having an irradiation dose of 5-50 kGy to obtain a grafted polyolefin material, wherein heteroatoms are introduced into the grafted polyolefin material after the treatment;
[0008] Step 3: washing the grafted polyolefin material described in step 2 to remove the polymer on the surface of the grafted polyolefin material;
[0009] Step 4: subjecting the grafted polyolefin material washed in step 3 to high-temperature carbonization treatment to obtain a hard carbon material.
[0010] In a preferred embodiment, the radiation grafting solution includes radiation grafting monomers, the concentration of the radiation grafting monomers is 5%-50%, and the solvent of the radiation grafting solution can be anhydrous ethanol.
[0011] In a preferred embodiment, the concentration of the radiation grafted monomer is 10%.
[0012] In a preferred embodiment, the radiation grafting monomer is any one of oxygen (O2), polyethylene glycol diacrylate (PEGDA), glycidyl methacrylate (GMA), and phenolic resin (PF), preferably glycidyl methacrylate (GMA).
[0013] In a preferred embodiment, the high temperature carbonization in step 3 adopts programmed temperature increase with a heating rate of 2-10°C / min, and the high temperature carbonization is performed at 900-1500°C for 6 hours.
[0014] In a preferred embodiment, the high temperature carbonization in step 3 adopts programmed temperature increase with a heating rate of 2°C / min, and the high temperature carbonization is performed at 1300°C for 6 hours.
[0015] In a preferred embodiment, the polyolefin material includes any one of polyethylene materials (PE), polypropylene materials (PP), polypropylene-polyethylene materials (PE-PP), and polypropylene-polyethylene-polypropylene materials (PP-PE-PP).
[0016] In order to solve the above technical problems, the present invention also provides a sodium ion battery negative electrode hard carbon material, and the negative electrode material is prepared by the above preparation method.
[0017] In order to solve the above technical problems, the present invention also provides a sodium ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the negative electrode comprises the above-mentioned sodium ion battery negative electrode hard carbon material.
[0018] Compared with the prior art, the present invention has the following advantages:
[0019] 1. The method for preparing the hard carbon material for the negative electrode of the sodium ion battery provided by the present invention innovatively adopts the radiation grafting method to introduce heteroatoms into the polyolefin material, thereby improving the hard carbon yield and increasing the economic benefits.
[0020] 2. The method for preparing the hard carbon material for the negative electrode of a sodium ion battery provided by the present invention is simple to operate, uses waste polyolefin materials as raw materials, and has low cost.
[0021] 3. The negative electrode hard carbon material prepared by the preparation method provided by the present invention has stable properties, good cycle performance and rate performance, and has broad application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 FT-IR images of the polyolefin material before and after irradiation grafting in Example 1 are compared;
[0023] Figure 2 is the XRD pattern of the hard carbon material prepared in Example 1;
[0024] Figure 3 This is a SEM image of the hard carbon material prepared in Example 1;
[0025] Figure 4 The charge and discharge cycle curve of a sodium ion battery using the pole piece made of the hard carbon material prepared in Example 1 as the working electrode. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0027] The embodiments of the present invention are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and processes are given, but the protection scope of the present invention is not limited to the following embodiments. Unless otherwise specified, the equipment, reagents, processes, parameters, etc. involved in the present invention are conventional equipment, reagents, processes, parameters, etc., and are no longer used as embodiments.
[0028] The endpoints and any value of the scope disclosed in the present invention are not limited to this accurate scope or value, and these scopes or values should be understood to include values close to these scopes or values. All scopes cited by the present invention include all point values within the scope. For numerical ranges, between the endpoint values of each scope, between the endpoint values of each scope and a separate point value, and between separate point values, one or more new numerical ranges can be combined with each other, and these numerical ranges should be considered as specifically disclosed in the present invention.
[0029] Example 1
[0030] This embodiment provides a method for preparing a sodium ion battery negative electrode hard carbon material, comprising the following steps:
[0031] Step 1: Pretreatment: The waste polyolefin material is placed in anhydrous ethanol solvent and soaked for 2 hours for ultrasonic treatment, then washed with anhydrous ethanol, transferred to a beaker and placed in a 60°C oven for drying for 12 hours to obtain a pretreated polyolefin material. The pretreated polyolefin material removes impurities covering the surface.
[0032] Step 2: Radiation grafting: A 10% mass concentration of glycidyl methacrylate (GMA) anhydrous ethanol solution is prepared as an irradiation grafting solution, and the polyolefin material pretreated in step 1 is placed therein. A neutron beam irradiation dose of 30 kGy is used to perform irradiation grafting treatment on the polyolefin material soaked in the glycidyl methacrylate (GMA) anhydrous ethanol solution, so as to introduce heteroatoms into the polyolefin material. After the heteroatoms are introduced through the irradiation grafting treatment, a grafted polyolefin material is obtained. The FTIR graph of the grafted polyolefin material obtained through the irradiation grafting treatment is as follows: Figure 1 shown.
[0033] Step 3: Cleaning: Wash the grafted polyolefin material after irradiation with anhydrous ethanol to remove the monomers or polymers that have not been grafted, and then place it in a beaker and dry it in an oven at 60° C. for 12 hours. Weigh the dried grafted polyolefin material to obtain the raw material mass m1.
[0034] Step 4: High-temperature carbonization: The grafted polyolefin material that has been cleaned in step 3 is placed in a porcelain boat and placed in a fiber-type tube furnace for high-temperature carbonization. The temperature is programmed to rise at a rate of 2°C / min, and high-temperature carbonization is performed at 1300°C for 6 hours to obtain a hard carbon material. The XRD pattern of the prepared hard carbon material is shown in FIG. Figure 2 The SEM image is shown in Figure 3. The obtained hard carbon material is weighed to obtain the hard carbon mass m2. After calculation, the carbon yield of this embodiment is 10.4%. (The carbon yield is the ratio of the hard carbon mass to the raw material mass, that is, the carbon yield η = m2 / m1*100%)
[0035] Weigh 0.8g of the prepared hard carbon material, add 0.1g of acetylene black and 0.1g of polyvinylidene fluoride and evenly disperse them in nitrogen methyl pyrrolidone, stir evenly and apply them on copper foil with a scraper to make a pole piece, place the pole piece on an 80℃ hot plate to dry for 10 minutes, and then transfer it to an 80℃ oven for vacuum drying for 12 hours. The dried pole piece is cut into a pole piece with a diameter of 12mm, placed in an argon atmosphere glove box, and assembled into a sodium ion button battery with a metal sodium sheet as the counter electrode, Whatman glass fiber as the diaphragm, and 140mL of 1MNaPF6 / DME as the electrolyte.
[0036] The sodium ion button battery assembled above was charged and discharged at a current density of 20 mA / g. The sodium ion battery in this embodiment has a reversible capacity of 308 mAh / g and excellent performance. The charge and discharge cycle curve of this embodiment is shown in FIG. Figure 4 shown.
[0037] Example 2
[0038] The hard carbon preparation and sodium ion button battery assembly process of this embodiment are the same as those of Example 1, with the only difference being that the radiation grafting monomer used in this embodiment is polyethylene glycol diacrylate (PEGDA).
[0039] Example 3
[0040] The hard carbon preparation and sodium ion button battery assembly process of this embodiment are the same as those of Example 1, with the only difference being that the radiation grafting monomer used in this embodiment is phenolic resin (PF).
[0041] Example 4
[0042] The hard carbon preparation and sodium ion button battery assembly process of this embodiment are the same as those of Example 1, with the only difference being that the radiation grafting monomer used in this embodiment is oxygen (O2).
[0043] The hard carbon yields and sodium ion battery performances of Examples 1-4 were compared to obtain Table 1:
[0044] Table 1: Comparison of hard carbon yield and performance of different irradiated grafted monomers
[0045] serial number Irradiated monomer Carbon yield (%) Specific capacity (mAh / g) Example 1 GMA 10.4 368 Example 2 PEDGA 5.3 330 Example 3 PF 9.7 210 Example 4 <![CDATA[O2]]> 4.6 342
[0046] It can be seen from Table 1 that the use of different irradiation grafting monomers has an effect on the hard carbon yield and specific capacity. Among them, the use of glycidyl methacrylate (GMA) as the irradiation grafting monomer to prepare the hard carbon material has the highest carbon yield and the highest specific capacity after being made into the negative electrode.
[0047] Example 5
[0048] The hard carbon preparation and sodium ion button battery assembly process of this embodiment are the same as those of Example 1, the only difference being that the concentration of the irradiation grafting monomer of the irradiation grafting solution of this embodiment is different. This embodiment uses a 5% mass concentration of glycidyl methacrylate (GMA) anhydrous ethanol solution as the irradiation grafting solution.
[0049] Example 6
[0050] The hard carbon preparation and sodium ion button battery assembly process of this embodiment are the same as those of Example 1, the only difference being that the concentration of the irradiation grafting monomer of the irradiation grafting solution of this embodiment is different. This embodiment uses a 20% mass concentration of glycidyl methacrylate (GMA) anhydrous ethanol solution as the irradiation grafting solution.
[0051] Example 7
[0052] The hard carbon preparation and sodium ion button battery assembly process of this embodiment are the same as those of Example 1, the only difference being that the concentration of the irradiation grafting monomer of the irradiation grafting solution of this embodiment is different. This embodiment uses a 30% mass concentration of glycidyl methacrylate (GMA) anhydrous ethanol solution as the irradiation grafting solution.
[0053] The hard carbon yield and sodium ion battery performance of Example 1 and Examples 5-7 were compared to obtain Table 2:
[0054] Table 2: Comparison of hard carbon yield and performance at different irradiation grafting monomer concentrations
[0055] serial number Monomer concentration (%) Carbon yield (%) Specific capacity (mAh / g) Example 1 10% 10.4 368 Example 5 5% 7.9 340 Example 6 20% 11.1 354 Example 7 30% 11.4 328
[0056] It can be seen from Table 2 that different irradiation grafting monomer concentrations have an effect on the hard carbon yield and specific capacity. Among them, the carbon yield using 30% monomer concentration is the highest, but its specific capacity is the lowest; the carbon yield using 10% monomer concentration is also high, and the hard carbon negative electrode made by it has the highest specific capacity and the best comprehensive performance.
[0057] Example 8
[0058] The hard carbon preparation and sodium ion button battery assembly process of this embodiment are the same as those of Example 1, with the only difference being the irradiation dose of this embodiment. This embodiment uses a neutron beam irradiation dose of 5 kGy to perform irradiation grafting treatment on the polyolefin material soaked in an anhydrous ethanol solution of glycidyl methacrylate (GMA).
[0059] Example 9
[0060] The hard carbon preparation and sodium ion button battery assembly process of this embodiment are the same as those of Example 1, with the only difference being the irradiation dose of this embodiment. This embodiment uses a neutron beam irradiation dose of 10 kGy to perform irradiation grafting treatment on a polyolefin material soaked in an anhydrous ethanol solution of glycidyl methacrylate (GMA).
[0061] Example 10
[0062] The hard carbon preparation and sodium ion button battery assembly process of this embodiment are the same as those of Example 1, with the only difference being the irradiation dose of this embodiment. This embodiment uses a neutron beam irradiation dose of 20 kGy to perform irradiation grafting treatment on the polyolefin material soaked in an anhydrous ethanol solution of glycidyl methacrylate (GMA).
[0063] Embodiment 11
[0064] The hard carbon preparation and sodium ion button battery assembly process of this embodiment are the same as those of Example 1, and the only difference is that the irradiation dose of this embodiment is different. This embodiment uses a neutron beam irradiation dose of 50 kGy to perform irradiation grafting treatment on the polyolefin material soaked in an anhydrous ethanol solution of glycidyl methacrylate (GMA).
[0065] The hard carbon yield and sodium ion battery performance of Example 1 and Examples 8-11 are compared to obtain Table 3:
[0066] Table 3: Comparison of hard carbon yield and performance at different irradiation doses
[0067] serial number Radiation dose (kGy) Carbon yield (%) Specific capacity (mAh / g) Example 1 30 10.4 368 Example 8 5 7.6 345 Example 9 10 8.3 350 Example 10 20 9.2 355 Embodiment 11 50 10.7 347
[0068] It can be seen from Table 3 that different irradiation doses have an effect on the hard carbon yield and specific capacity. Among them, the carbon yield using an irradiation dose of 50 kGy is the highest, but its specific capacity is lower; the carbon yield using an irradiation dose of 30 kGy is also higher, and the hard carbon negative electrode produced by it has the highest specific capacity and the best comprehensive performance.
[0069] Example 12
[0070] The hard carbon preparation and sodium ion button battery assembly process of this embodiment are the same as those of Example 1, with the only difference being that the carbonization temperature during programmed heating in this embodiment is different. This embodiment adopts programmed heating with a heating rate of 2°C / min, and high-temperature carbonization is performed at 900°C for 6 hours to obtain a hard carbon material.
[0071] Embodiment 13
[0072] The hard carbon preparation and sodium ion button battery assembly process of this embodiment are the same as those of Example 1, with the only difference being that the carbonization temperature during programmed heating in this embodiment is different. This embodiment adopts programmed heating with a heating rate of 2°C / min, and high-temperature carbonization is performed at 1000°C for 6 hours to obtain a hard carbon material.
[0073] Embodiment 14
[0074] The hard carbon preparation and sodium ion button battery assembly process of this embodiment are the same as those of Example 1, with the only difference being that the carbonization temperature during programmed heating in this embodiment is different. This embodiment adopts programmed heating with a heating rate of 2°C / min, and high-temperature carbonization is performed at 1100°C for 6 hours to obtain a hard carbon material.
[0075] Embodiment 15
[0076] The hard carbon preparation and sodium ion button battery assembly process of this embodiment are the same as those of Example 1, with the only difference being that the carbonization temperature during programmed heating in this embodiment is different. This embodiment adopts programmed heating with a heating rate of 2°C / min, and high-temperature carbonization is performed at 1200°C for 6 hours to obtain a hard carbon material.
[0077] Example 16
[0078] The hard carbon preparation and sodium ion button battery assembly process of this embodiment are the same as those of Example 1, with the only difference being that the carbonization temperature during programmed heating in this embodiment is different. This embodiment adopts programmed heating with a heating rate of 2°C / min, and high-temperature carbonization is performed at 1400°C for 6 hours to obtain a hard carbon material.
[0079] Embodiment 17
[0080] The hard carbon preparation and sodium ion button battery assembly process of this embodiment are the same as those of Example 1, with the only difference being that the carbonization temperature during programmed heating in this embodiment is different. This embodiment adopts programmed heating with a heating rate of 2°C / min, and high-temperature carbonization is performed at 1500°C for 6 hours to obtain a hard carbon material.
[0081] The hard carbon yield and sodium ion battery performance of Example 1 and Examples 12-17 are compared to obtain Table 4:
[0082] Table 4: Comparison of hard carbon yield and performance at different carbonization temperatures
[0083] serial number Carbonization temperature(℃) Carbon yield (%) Specific capacity (mAh / g) Example 1 1300 10.4 368 Example 12 900 12 267 Embodiment 13 1000 11.4 303 Embodiment 14 1100 11.1 310 Embodiment 15 1200 10.6 336 Example 16 1400 9.5 342 Embodiment 17 1500 6.7 314
[0084] It can be seen from Table 4 that different carbonization temperatures have an effect on the hard carbon yield and specific capacity. The carbon yield at a carbonization temperature of 1000°C is the highest, but its specific capacity is low; the carbon yield obtained at a carbonization temperature of 1300°C is also high, and the hard carbon negative electrode produced has the highest specific capacity and the best comprehensive performance.
[0085] Embodiment 18
[0086] The hard carbon preparation and sodium ion button battery assembly process of this embodiment are the same as those of Example 1, with the only difference being the heating rate during programmed heating in this embodiment. This embodiment adopts programmed heating with a heating rate of 5°C / min, and high-temperature carbonization is performed at 1300°C for 6 hours to obtain a hard carbon material.
[0087] Embodiment 19
[0088] The hard carbon preparation and sodium ion button battery assembly process of this embodiment are the same as those of Example 1, with the only difference being the heating rate during programmed heating in this embodiment. This embodiment adopts programmed heating with a heating rate of 10°C / min, and high-temperature carbonization is performed at 1300°C for 6 hours to obtain a hard carbon material.
[0089] The hard carbon yield and sodium ion battery performance of Example 1 and Examples 18-19 are compared to obtain Table 5:
[0090] Table 5: Comparison of hard carbon yield and performance at different heating rates
[0091] serial number Heating rate (℃ / min) Carbon yield (%) Specific capacity (mAh / g) Example 1 2 10.4 368 Embodiment 18 5 10.1 345 Embodiment 19 10 9.8 353
[0092] It can be seen from Table 5 that different heating rates during programmed temperature heating have an impact on the hard carbon yield and specific capacity. Among them, the carbon yield is the highest when the heating rate is 2°C / min, and the specific capacity after the negative electrode is made is the highest.
[0093] The synthesis method of the hard carbon material provided by the present invention is simple and easy to operate, and uses waste polyolefin materials as raw materials, which is low in cost; at the same time, the method of irradiation grafting is innovatively adopted to introduce heteroatoms into the polyolefin material, thereby increasing the hard carbon yield and the economic benefits. The hard carbon material prepared by the present invention is low in cost, stable in nature, has good cycle performance and rate performance, has a wide range of application scenarios, and has great potential in the recovery of polyolefin materials and the application of sodium ion batteries.
[0094] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.
Claims
1. A method for preparing a sodium ion battery negative electrode hard carbon material, characterized in that: The following steps are involved: Step 1: adding a polyolefin material to a solvent and soaking it for ultrasonic treatment, washing the treated polyolefin material and drying it to obtain a pretreated polyolefin material; Step 2: adding the pretreated polyolefin material in step 1 to an irradiation grafting solution and performing irradiation grafting treatment with a neutron beam having an irradiation dose of 5-50 kGy to obtain a grafted polyolefin material; the irradiation grafting solution comprises an irradiation grafting monomer, and the irradiation grafting monomer is any one of oxygen, polyethylene glycol diacrylate, glycidyl methacrylate, and phenolic resin; Step 3: washing the grafted polyolefin material in step 2 to remove the monomers or polymers that have not been grafted; Step 4: subjecting the washed grafted polyolefin material in step 3 to high-temperature carbonization treatment to obtain a hard carbon material.
2. The method for preparing the hard carbon material for the negative electrode of a sodium ion battery according to claim 1, characterized in that: The concentration of the radiation grafted monomer is 5%-50%.
3. The method for preparing the hard carbon material for the negative electrode of a sodium ion battery according to claim 2, characterized in that: The concentration of the radiation grafted monomer is 10%.
4. The method for preparing the sodium ion battery negative electrode hard carbon material according to claim 1, characterized in that: The high temperature carbonization in step 3 adopts programmed temperature increase with a heating rate of 2-10°C / min, and the high temperature carbonization is carried out at 900-1500°C for 6 hours.
5. The method for preparing the hard carbon material for the negative electrode of a sodium ion battery according to claim 4, characterized in that: The high temperature carbonization in step 3 adopts programmed temperature increase with a heating rate of 2°C / min, and the high temperature carbonization is carried out at 1300°C for 6 hours.
6. The method for preparing the hard carbon material for the negative electrode of a sodium ion battery according to claim 1, characterized in that: The polyolefin material includes any one of polyethylene materials, polypropylene materials, polypropylene-polyethylene materials, and polypropylene-polyethylene-polypropylene materials.
7. A sodium ion battery negative electrode hard carbon material, characterized in that: The negative electrode hard carbon material is prepared by the preparation method described in any one of claims 1-6.
8. A sodium ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, characterized in that: The negative electrode comprises the sodium ion battery negative electrode hard carbon material according to claim 7.
Citation Information
Patent Citations
Hard carbon negative electrode material of lithium ion battery, preparation method and application of hard carbon negative electrode material
CN102820455A
Production method and application of lithium battery
CN112366359A